1997
DOI: 10.1021/jp9701606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Vanadium Oxide-Catalyzed Selective Reduction of NO by NH3. A Quantum Chemical Modeling

Abstract: Quantum chemical calculations have been performed using density functional theory to model the mechanism of selective catalytic reduction of NO by NH 3 on vanadium oxide. The reaction is initiated by NH 3 adsorption on a Brønsted site modeled as a dimer cluster model representative of vanadium oxide, containing a terminal VdO adjacent to a V-OH group. The calculations indicate that the adsorbed NH 3 behaves as NH 4 + , which is supported by calculated IR spectra. Subsequently NO reacts with this activated NH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 65 publications
3
42
0
Order By: Relevance
“…In contrast to experimental results previous theoretical studies investigating NH 3 adsorption at the perfect V 2 O 5 (010) surface could only verify the presence of one strongly bound NH 4 + species [12][13][14][15][16][17][18][19] . Obviously, important details of the reaction mechanism have not yet been unveiled and essential questions, e.g.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast to experimental results previous theoretical studies investigating NH 3 adsorption at the perfect V 2 O 5 (010) surface could only verify the presence of one strongly bound NH 4 + species [12][13][14][15][16][17][18][19] . Obviously, important details of the reaction mechanism have not yet been unveiled and essential questions, e.g.…”
Section: Introductionmentioning
confidence: 69%
“…This includes hydrogen, nitrogen, NO, ammonia, as well as NH x species, x= 1, 2, 4 generated by (de)hydrogenation processes at the surface. Going beyond previous theoretical studies by others [12][13][14][15][16][17][18][19] where only sections of the perfect V 2 O 5 (010) surface have been examined, we considered also models for sections of the reduced surface due to oxygen vacancies. Our theoretical study showed that surface reduction strongly affects the adsorption properties and reduced sites may play an important role for the SCR reaction.…”
Section: Introductionmentioning
confidence: 99%
“…36 Since the KohnSham orbitals 21 give the total ground-state electron density of the system, they also provide a measure of both the global and local chemical reactivity of the system. 22,27,[37][38][39][40][41][42] The Fukui functions (FF) and related hardness/softness characteristics constitute the major chemical descriptors of molecular species for open systems, in which the number of electrons is a continuous equilibrium variable. 22 In the frozen core approximation the FF represent the density of the relevant frontier molecular orbital involved in electron receiving (nucleophilic attack) or withdrawing (electrophilic attack) processes.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Technologically relevant material properties of vanadium oxide compounds rely on the respective electronic state of the vanadium ion that can appear in different valence configurations leading to various applications such as electrodes in batteries, [1][2][3] thermochromic windows or IR protective shields, [4][5][6][7] catalysts for the oxidation of NO x or hydrocarbons, [8][9][10][11][12] and infrared detectors. [13,14] Vanadium oxide phases have been synthesized as one-, two-or three-dimensional materials by several methods such as sol-gel or other wet chemical techniques, [14][15][16] pulsed laser deposition, [17,18] sputtering or physical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%